IMPLEMENTASI LEGISLASI BENIH DALAM MENSUKSESKAN SWASEMBADA PANGAN - Valeriana Darwis (Universitas Sebelas Maret, 2016)
Seed has an important role to increasing the productivity of food crops and has has a lot of legislation issued by the government relating to seed. However, to date there are no known legislation from local government (PEMDA) on seed (specific location). At the current stage, the existing local legislation on seed was based on the initial legislation from the central government especially Cultivation Act No. 12/1992 and Government Legislation No.44/1995. To date the most important institution based on the existing legislation on seed is BPSBTPH (Seed Control and Certification Services Agency for Food Crops and Horticulture). BPSBTPH has a function to control and be responsible in seed production, from procurement, distribution and trading activities. To optimize their role and function the BPSBTPH should: (1) develop policy for agricultural enterprises or farmers who have been used un-labelled seed; (2) participate in supervising new seed products from other agencies; (3) more focus on supervising duties and less pressure on achieving target in production that was set by local government.